2002
DOI: 10.1159/000057874
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Distribution and Background Variables of Smooth-Bordered Tooth Wear in Teenagers in The Hague, The Netherlands

Abstract: The purposes of the study were: (1) to assess the prevalence and distribution of smooth-bordered tooth wear in teenagers, and (2) to investigate the relationship between smooth-bordered tooth wear and social background, dietary pattern, drinking habits, oral hygiene practices and caries prevalence. In The Hague, The Netherlands, a sample of 345 10- to 13-year-olds and 400 15- and 16-year-olds was clinically examined. The criteria for the assessment of smooth-bordered tooth wear (‘smooth wear’) were in line wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
96
4
29

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(153 citation statements)
references
References 16 publications
23
96
4
29
Order By: Relevance
“…Most studies have reported the incidence to be more common in males [13]. In the present study also, out of 570 patients examined 131 (45%) patients were male and 114 (41%) were female.…”
Section: Graphsupporting
confidence: 60%
“…Most studies have reported the incidence to be more common in males [13]. In the present study also, out of 570 patients examined 131 (45%) patients were male and 114 (41%) were female.…”
Section: Graphsupporting
confidence: 60%
“…Although not widely documented regarding dental erosive wear, sour sweets have been suggested to be a contributor too important to disregard [35] [36]. Some researchers have not found a relationship between dental erosion and fruit and acidic drinks [37] [38]. There was growing evidence in the UK, that a major cause of tooth erosion is gastroesophageal reflux, [39].…”
Section: Discussionmentioning
confidence: 99%
“…Since enamel is >90% hydroxyapatite by volume, it is vulnerable to chemical attack from acids, dissolving readily when the oral pH falls below 5.5. The erosion of enamel has become a serious problem in modern human populations [1,2,3,4,5,6,7], being attributed mainly to the consumption of acidic carbonated soda drinks [8]. However, gastric regurgitation [9] is also of increasing importance as a cause, particularly as the incidence of gastro-oesophageal reflux in the population increases with an increasing trend towards obesity [10].…”
Section: Introductionmentioning
confidence: 99%